Assessing Financial Management Centralization in Multicorporate Enterprises (Groups of Companies): Methodological Potential of Traditional Financial Performance Indicators - Ramil R. Vasikov; Svetlana V. Yudina (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
In conditions of volatile cash flow caused by external factors, multicorporate enterprises need to look for new methods of optimal financial distribution. This is especially important for multi-industry organizational entities that want to ensure their solvency and liquidity. Centralized financial management eases the complex distribution of management objects, i.e., subsidiaries and dependent companies. The article describes the process of financial management centralization in large Russian conglomerates. The research objective was to develop a methodology for efficiency assessment based on open data and official financial statements of three groups of companies in the domestic fuel and energy sector. An attempt was made to assess the manageability of liquidity, stability, and profitability. Most manageability indicators were distributed unevenly among the enterprises within the conglomerates, more than a third of them sliding below the standard. However, the groups proved quite successful in managing receivables and payables, which indicates good prospects for further search for methodological solutions in centralization efficiency assessment for multicorporate enterprises.